2013
DOI: 10.1093/jmcb/mjt043
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/ -catenin signaling in midbrain dopaminergic neuron specification and neurogenesis

Abstract: Loss of midbrain dopaminergic (mDA) neurons underlies the motor symptoms of Parkinson's disease. Towards cell replacement, studies have focused on mechanisms underlying embryonic mDA production, as a rational basis for deriving mDA neurons from stem cells. We will review studies of β-catenin, an obligate component of the Wnt cascade that is critical to mDA specification and neurogenesis. mDA neurons have a unique origin--the midbrain floor plate (FP). Unlike the hindbrain and spinal cord FP, the midbrain FP is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 75 publications
2
72
0
Order By: Relevance
“…Among these mutated genes, transcriptional factor HESX1 ‐mediated repression of Wnt/β‐catenin targets is required for the normal development of anterior forebrain 24; Wnt/β‐catenin signalling promotes midbrain dopaminergic progenitor specification, proliferation and neurogenesis by up‐regulating OTX2 in progenitors 25; Notch signalling has been linked to PROP1 expression 26; GPR161 and CDON , the latest mutations found in patients with PSIS by WES recently, are regulators of Shh pathway 27, 28. Collectively, these pathways seem to be critical to pituitary development.…”
Section: Discussionmentioning
confidence: 99%
“…Among these mutated genes, transcriptional factor HESX1 ‐mediated repression of Wnt/β‐catenin targets is required for the normal development of anterior forebrain 24; Wnt/β‐catenin signalling promotes midbrain dopaminergic progenitor specification, proliferation and neurogenesis by up‐regulating OTX2 in progenitors 25; Notch signalling has been linked to PROP1 expression 26; GPR161 and CDON , the latest mutations found in patients with PSIS by WES recently, are regulators of Shh pathway 27, 28. Collectively, these pathways seem to be critical to pituitary development.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing CNS, DA neurons arise from the mesodiencephalic floor plate (mdFP), here defined by the co-expression of Shh, Foxa2 and Lmx1a rostral to the midbrain-hindbrain boundary (MHB), due to the concerted action of Shh, Fgf and Wnt signaling pathways (Arenas et al, 2015;Blaess and Ang, 2015;Joksimovic and Awatramani, 2014;Lahti et al, 2012;Luo and Huang, 2016;Smits et al, 2006;Wurst and Prakash, 2014). In terms of boundaries delimiting the DA progenitor zone, several studies have demonstrated that the caudal limit of DA neuron production is at the MHB defined by the caudal limit of Otx2 expression (Brodski et al, 2003;Joyner et al, 2000;Simeone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, WNT1-mediated β-catenin signaling controls the correct differentiation of mdDA progenitors/precursors into mature mdDA neurons through the direct activation of Lmx1a (Chung et al, 2009;Joksimovic et al, 2009;Prakash et al, 2006;Tang et al, 2009Tang et al, , 2010Joksimovic and Awatramani, 2014;Wurst and Prakash, 2014). Murine LMX1A, in turn, binds to and activates the transcription of the Wnt1, Pitx3 and Nr4a2 promoters (Chung et al, 2009;Wurst and Prakash, 2014;our own unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…Shh secreted from the floor plate (FP) is required for the establishment of progenitor domains in ventral mesencephalon (Blaess et al, 2006;Perez-Balaguer et al, 2009). However, to generate mdDA neurons Wnt/β-catenin signaling has to suppress expression of Shh in this region (Joksimovic et al, 2009;Joksimovic and Awatramani, 2014;Wurst and Prakash, 2014). Wnt1/β-catenin signaling also sequentially induces the expression of several transcription factors (TFs) in postmitotic mdDA precursors, such as Lmx1a and Pitx3, both of which are necessary for proper mdDA neuron development (Blaess and Ang, 2015;Hegarty et al, 2013;Veenvliet and Smidt, 2014;Wurst and Prakash, 2014).…”
Section: Introductionmentioning
confidence: 99%